Electroplastic effect associated with the dislocation generation in the initially dislocation-free silicon filamentary crystals - Ermakov, A.P.; Darinsky, B.M.; Drozhzhin, A.I. (Functional Materials, 2004)
Experiments on local high-intensity electric current pulse action on mechanical properties of a Si filamentary crystal made it possible to reveal a novel type of electroplastic effect associated with the generation of dislocations. Эксперименты по локальному высокоинтенсивному воздействию импульсом электрического тока на механические свойства нитевидных кристаллов Si позволили обнаружить новую разновидность электропластического эффекта, связанного с зарождением дислокаций. Експерименти з локального високоінтєнсивного впливу імпульсом електричного струму на механічні властивості ниткоподібного кристалу кремнію дозволили виявити новий різновид електропластичного ефекту, пов’язаного з зародженням дислокацій.